A Continuum of Older Women's Experiences as Members of Alcoholics Anonymous (AA): A Qualitative Analysis. Issue 1 (2nd January 2021) - Sanders, Jolene
ABSTRACT: This qualitative analysis looks at women across a continuum of sobriety and affiliation with Alcoholics Anonymous (AA). The sample frame consists of 60 women's stories as submitted to the Grapevine: The International Journal of Alcoholics Anonymous and explores older women's recovery experiences within the context of AA. An intersectional interpretive lens is offered in order to look at both gender and age as they relate to recovery from alcohol use disorder (AUD). Findings suggest a comparative difference not only among older women as a group seeking recovery but between those who have late-onset AUD, those who sought help in middle-age, and those women with long-term sobriety affiliated with AA for 20 or more years.